Effects of Radiation on Materials: 21st International Symposium 2004
DOI: 10.1520/stp11267s
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mechanical Properties of High-Purity V-4Cr-4Ti-Si, Al, Y Alloys after Neutron Irradiation at Relatively Low Temperatures

Abstract: Mechanical properties after neutron irradiation of V-4Cr-4Ti-0.1Si-0.1Al-0.1Y and V-4Cr-4Ti-0.1Si-0.1Al-0.3Y alloys (nominal weight percentage) were studied. Neutron irradiation was carried out at 290°C to 8×1022 n/m2 (E>1 MeV, about 0.014 dpa) in the Japan Materials Testing Reactor (JMTR). Tensile tests were carried out using miniaturized specimens at ambient temperature and irradiation temperature. Charpy impact tests were conducted at temperatures from -196 to 0°C using an instrumented machine. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Y addition has little effect on irradiation hardening at 473 K. Watanabe et al [17] reported that dislocation loops were formed and no irradiation-induced Ti-CON precipitates after 2.4 MeV Cu 2+ ion-irradiation at 473 K to 0.25 dpa. Y addition suppressed irradiation-induced precipitation due to the reduction in interstitial impurities (so-called scavenging effect) and then improved ductility after neutron-irradiation [3][4][5]. Therefore, the scavenging effect of Y addition on the improvement of irradiation hardening is significant only in the temperature range where irradiation-induced precipitates are dominant, and is limited above the temperature between 200 and 400 o C.…”
Section: Nanoindentation Hardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Y addition has little effect on irradiation hardening at 473 K. Watanabe et al [17] reported that dislocation loops were formed and no irradiation-induced Ti-CON precipitates after 2.4 MeV Cu 2+ ion-irradiation at 473 K to 0.25 dpa. Y addition suppressed irradiation-induced precipitation due to the reduction in interstitial impurities (so-called scavenging effect) and then improved ductility after neutron-irradiation [3][4][5]. Therefore, the scavenging effect of Y addition on the improvement of irradiation hardening is significant only in the temperature range where irradiation-induced precipitates are dominant, and is limited above the temperature between 200 and 400 o C.…”
Section: Nanoindentation Hardnessmentioning
confidence: 99%
“…In order to improve the irradiation embrittlement, yttrium (Y) was added to reduce the interstitial oxygen due to the formation of Y2O3. It has been reported that Y addition was effective to improve ductility after neutron-irradiation [3,4], while neutron-irradiation data are too few to prove how much Y addition is effective in irradiation condition of lower temperature region and of high-dose [5]. The effect of Y addition on irradiation hardening in lower temperature region and at high-dose was still unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that small addition of yttrium (Y) was effective to reduce oxygen impurity and improve ductility after neutron irradiation without severe degradation of low-temperature impact properties. [2][3][4][5] Y addition, on the other hand, can also degrade hightemperature strength, because Y could scavenge solute oxygen, which is a strong hardening agent in vanadium alloys, by a formation of Y 2 O 3 (Ref. 2).…”
Section: Introductionmentioning
confidence: 99%